IDENTIFICATION OF STUDENTS' MISCONCEPTIONS ON INTEGRAL TOPIC USING A FOUR-TIER DIAGNOSTIC TEST - Rahmawati, Fadhilah; Pamungkas, Megita Dwi; Ardianto, Bagas; Fadhilatullathifi, Zakkiyatun Nisa; Gunawan, Gunawan; Safitri, Ditaul (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Abstract: Every student has a different ability to understand mathematical concepts, thus affecting the students' misconceptions. The research aims to identify the misconceptions using a four-tier diagnostics test method in integral topic. This research uses the qualitative method with study case strategy. The data are obtained from the four-tier diagnostic test on the integral topic. The subjects in this research are XII grade students at MAN Kota Magelang. The research results show that students' misconceptions divided into several categories of misconceptions, namely misconceptions, did not understand concepts, understood some concepts, understood concepts, and were undefined. The cause of students experiencing misconceptions on integral topics is that there are too many formulas to be memorized by students, and teacher learning methods are less attractive to students' learning interests on integral topics. Abstrak: Setiap siswa memiliki kemampuan berbeda untuk memahami konsep matematika, sehingga memengaruhi kesalahpahaman pada siswa. Penelitian ini bertujuan untuk mengidentifikasi kesalahpahaman dengan metode uji diagnostik empat-tingkat dalam materi integral. Penelitian ini menggunakan metode kualitatif dengan strategi studi kasus. Data diperoleh dari uji diagnostik empat-tingkat pada materi integral. Subjek penelitian ini adalah siswa kelas XII di MAN Kota Magelang. Hasil penelitian menunjukkan bahwa beberapa kategori kesalahpahaman, yaitu kesalahpahaman, tidak memahami konsep, memahami beberapa konsep, memahami konsep, dan tidak terdefinisi. Penyebab siswa mengalami kesalahpahaman tentang materi integral adalah bahwa ada banyak rumus yang harus dihafal oleh siswa dan metode pembelajaran guru kurang menarik bagi minat belajar siswa pada materi integral.